Tám 8 steps to high performance - Effron, Marc (Harvard Business Review Press, 2018)
In 8 Steps to High Performance, talent expert and bestselling author Marc Effron cuts through the noise with his signature "science-based simplicity" approach to identify what matters most and show you how to optimally apply your time and effort to boost your performance. It turns out that higher performance comes from doing many things well--but some of those things are not in your power to change. Effron reveals the eight key factors you do control and practical steps for improving yourself on each one